2008
DOI: 10.1097/wad.0b013e31818ecbbc
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exercise on Negative Affect in Residents in Special Care Units With Moderate to Severe Dementia

Abstract: Approximately 35% of individuals with dementia exhibit depression and/or anxiety symptoms, often manifested by symptoms of negative affect. Exercise has been associated with improved affect but has not been demonstrated to improve affect in residents of secured dementia units in long-term care facilities. This pilot study determined whether moderate-intensity, chair-based exercise was associated with changes in negative affect in residents in secured units. The sample included 36 patients from 2 nursing homes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 35 publications
0
37
1
1
Order By: Relevance
“…In depression, Aman and Thomas (2009) found no improvements in depressed mood after three weeks of engaging in exercise and a pilot study by Steinberg et al (2009) found evidence of higher depression scores and poorer quality of life after 12 weeks of daily aerobic exercise. Edwards et al (2008) failed to find a short-term effect of exercise, although after a 12-week period a significant effect was evident. Indeed, after a longer duration, significant effects accruing from exercise appear more likely.…”
Section: General Findingscontrasting
confidence: 50%
See 2 more Smart Citations
“…In depression, Aman and Thomas (2009) found no improvements in depressed mood after three weeks of engaging in exercise and a pilot study by Steinberg et al (2009) found evidence of higher depression scores and poorer quality of life after 12 weeks of daily aerobic exercise. Edwards et al (2008) failed to find a short-term effect of exercise, although after a 12-week period a significant effect was evident. Indeed, after a longer duration, significant effects accruing from exercise appear more likely.…”
Section: General Findingscontrasting
confidence: 50%
“…Indeed, there is some evidence that physical activity can help to reduce aggressive behaviors in people with dementia. Although Edwards et al (2008) found no effect of chair-based exercise in reducing levels of agitation after 12 weeks, Aman and Thomas (2009) training, and Volicer et al (2006) found that meaningful exercise (i.e. exercise designed to meet the interest, physical, mental, and psychosocial wellbeing of each resident) reduced agitation after seven months.…”
Section: General Findingsmentioning
confidence: 95%
See 1 more Smart Citation
“…For instance, some studies report the greatest benefits after multicomponent exercise interventions (e.g., combined strength and aerobic exercises) [32,42], while other studies consider aerobic exercise to be the driving force for improvements in cognition, physical functions, mood, and behavioral problems [1,2,12]. Regarding the duration, there is some evidence that short-term exercise interventions (< 12 weeks) are more likely to benefit mood and behavioral problems [9], while other studies report benefits on these outcomes only after 12 weeks of exercise [36,50]. Despite the heterogeneity, there is some consensus that the largest improvements in function are found after multicomponent interventions with a duration of at least 12 weeks, with larger effect sizes (ES) found in interven-…”
Section: Introductionmentioning
confidence: 93%
“…A widely applied type of physical activity for the oldest age group in, for example, long-term care is a group activity that is performed on and behind a chair (chair-assisted exercises) to guarantee safety (Edwards, Gardiner, Ritchie, Baldwin, & Sands, 2008), as older people may have balance problems (Deandrea et al, 2010). For many other daily activities the intensity is known (Ainsworth et al, 2000), but it is unclear whether chair-assisted exercise for older adults is of (at least) moderate intensity-the recommended intensity level for healthy aging.…”
mentioning
confidence: 99%